Islamic, Historical and Cultural Consciousness in Asad Muhammad Khan’s Stories: A Critical Review: اسد محمد خان کے افسانوں میں اسلامی، تاریخی و تہذیبی شعور: ایک تنقیدی جائزہ - Sadia, Miss Haleema (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
Asad Muhammad Khan is considered an important intellectual of Urdu. He born in India and then migrated to Pakistan in 1950. His work is mostly related to the historical events occurred during the partition of India. He emphasized the historical perspective of the people and stated that human life is very important and evolutionary. He is very important story t writer and in his different stories he describes several event of the kings of Delhi Sultans and gave these events a historical touch to increase the interest of the readers. He also authored about the different historical events related to the Islamic history as the initial phase of Islam the tregidy of Karbala. This article covers the intellectual work of Asad Muhammad Khan.